PALYNOLOGY: A FORENSIC TRACE TOOL TO IDENTIFY A TEMPORAL COASTAL VEGETATION CHANGES (Revista Ifes Ciência, 2023)
The purpose of this paper was to identify the temporal vegetation changes at the mouth of the Jucu River (ES), southeastern Brazil using the palynology such as forensic trace tool. Thus, a sedimentary core was collected with a depth of 190 cm, and was used to perform pollen, sedimentary and C-14 dating analyses. The results showed the formation of four zones to describe the vegetation evolution and the environmental changes. The first zone started around two thousand years before present (BP), with sandy sediments, which is indicative of high energy flow. The analysis of the palynological profile indicated the presence of herbaceous vegetation. For the second and third zones, there were a predominance of silt-sandy sediment, with the installation of the mangrove. Finally, the fourth zone considers the period of half century until the present, marked by the presence of silt-clay sediment and predominance of herbaceous vegetation. Therefore, those results demonstrate a high application of the pollen analysis to describe the vegetation succession.